Teachers’ Compliance with the Use of English as Medium of Instruction in the Liberal Arts Department - Vicente Fernandez (JPAIR, 2019)
The use of English as a medium of instruction is growing so fast. This institutional research determined the teachers’ compliance with the use of English as a medium of instruction. The researcher made use of the questionnaires as the primary source and main data gathering instrument. The statistical tools used were the frequency count, percentage, weighted mean and average mean. The total population of the respondents was utilized.  The findings revealed that the respondents failed to comply with the use of English as the medium of instruction due to several factors, such as, majority of the faculty members were not motivated to initiate the use of English, no cooperation among subject teachers that they used mother tongue in communication instead of English, did not create a friendly environment in learning English, and failed to explore ways to improve and enhance their teaching. As recommended, the compliance should be elevated at all times, the faculty should find ways to enhance their knowledge and skills about the English language, and the administration should spearhead to conduct seminars and workshops on language training, and create policies to oblige the faculty to use English as the medium of instruction and communication.